A membrane protein, TMCO5A, has a close relationship with manchette microtubules in rat spermatids during spermiogenesis. Issue 3 (17th January 2019) - Kaneko, Takane; Minohara, Taisuke; Shima, Sakurako; Yoshida, Kaori; Fukuda, Atsuko; Iwamori, Naoki; Inai, Tetsuichiro; Iida, Hiroshi
Abstract : We isolated the transmembrane and coiled‐coil domains 5A (Tmco5A) gene using polymerase chain reaction‐based subtraction technique and showed that Tmco5A was predominantly expressed in rat testes starting at 4 weeks of postnatal development. When expressed in COS7 cells, TMCO5A was found to be distributed in the endoplasmic reticulum‐nuclear membrane (ER‐NM) of cells as a membrane‐associated protein, while TMCO5AΔC lacking the transmembrane region (TM) mislocalized and diffused throughout the cytoplasm. The result suggested that TM is responsible for the retention of TMCO5A at the ER‐NM. Immunocytochemical and immunoblotting analyses indicated that TMCO5A was localized along the posterior part of the nuclei in both round and elongated rat spermatids but disappeared from epididymal spermatozoa. Double immunolabeling of isolated spermatids with the anti‐TMCO5A and the anti‐β tubulin antibodies showed that TMCO5A was always found to be closely associated with developing manchette microtubules but did not completely colocalize with them. On the other hand, we found that almost all TMCO5A colocalized with SUN4, a linker of nucleoskeleton and cytoskeleton complex protein present at the posterior part of spermatid nuclei. These data suggested that TMCO5A is located closer to the nuclei than the manchette microtubules. It is likely that TMCO5A, in association with manchette microtubules, is involved in the process of spermiogenesis. Abstract : Transmembrane and coiled‐coil domains 5A localized along the posterior part of spermatid nuclei is always in close association with developing manchette microtubules.